Pengaruh Brand Image, Harga dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen - Serlina Zuhrotul Azhariyah; Baju Pramutoko; Ririn Wahyu Arida (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the influence of Brand Image, Price, and Service Quality on Consumer Purchase Decisions at Vins Aesthetic Clinic Blitar. This research adopts a quantitative approach, focusing on the statistical analysis of the relationship between variables. The data were obtained from primary sources through the distribution of structured questionnaires to respondents. The population in this study consisted of all consumers of Vins Aesthetic Clinic Blitar. A sample of 100 respondents was selected using a saturated sampling technique, where the entire population is used as the sample due to the accessible number of consumers during the research period. Several analytical methods were applied, including validity and reliability tests to ensure the quality and consistency of the research instruments. Classical assumption tests were also conducted to confirm the appropriateness of the regression model. The study used multiple linear regression analysis to examine the effect of the independent variables — Brand Image, Price, and Service Quality — on the dependent variable, namely Consumer Purchase Decisions. The results of the partial (t-test) analysis showed that each variable — Brand Image, Price, and Service Quality — has a positive and significant influence on purchase decisions. Furthermore, the results of the simultaneous (F-test) analysis indicate that all three variables together significantly affect Consumer Purchase Decisions at Vins Aesthetic Clinic Blitar.